2014
DOI: 10.1111/febs.12802
|View full text |Cite
|
Sign up to set email alerts
|

Fusogenic properties of the ectodomains of hepatitis C virus envelope proteins

Abstract: We have used an isolated chimeric protein E1 340 E2 661 that includes the ectodomains of the envelope proteins of hepatitis C virus to study its interaction with model membranes. E1 340 E2 661 has some of the membrane destabilization properties, vesicle aggregation, lipid mixing and the release of internal aqueous content, which have previously been ascribed to fusion proteins. The effects are preferentially produced on vesicles of acidic phospholipids which would indicate the importance of the electrostatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Biochemical, spectroscopical and antigenic characterization of this isolated chimeric polypeptide indicated that E1 341 E2 661 behaved as a properly folded glycoprotein. Moreover, this chimera has been recently used as a tool to study the fusogenic properties of the HCV envelope proteins (Tello et al, 2014). In this report, a novel recombinant chimeric polypeptide, E2 661 E1 340 , has been produced.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical, spectroscopical and antigenic characterization of this isolated chimeric polypeptide indicated that E1 341 E2 661 behaved as a properly folded glycoprotein. Moreover, this chimera has been recently used as a tool to study the fusogenic properties of the HCV envelope proteins (Tello et al, 2014). In this report, a novel recombinant chimeric polypeptide, E2 661 E1 340 , has been produced.…”
Section: Discussionmentioning
confidence: 99%
“…The regions on both sides of the deletion were amplified separately by PCR, using the plasmid pAcGP67A-E2 661 E1 340 (Tello et al, 2014) as template. After co-purification of both PCR products, E2E1 192-267 and E1 293-340 , they were subjected to a second elongation PCR without primers in order to expand the area.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Fast-Basic extruder apparatus (Avestin, Inc.) with 100-nm polycarbonate filters (Costar) as previously described (Tello et al, 2014). Lipid concentration was calculated based on their phosphorous content determined according to Barlett (Barlett, 1959).…”
Section: Vesicle Preparationmentioning
confidence: 99%
See 2 more Smart Citations